Faktor-faktor yang Mempengaruhi Keberhasilan Sistem Informasi Akuntansi - Hadisoebroto, Andreas Emmanuel (Jurnal Widya Manajemen & Akuntansi, 2004)
The objective of this study is to know the condition of existence of AIS in PDAM. The second objective of this study is to examine relationship or correlation between those influencing factors and AIS success using Pearson's correlation product moment method. The third objective will examine the influence of each influencing factor to AIS success.